ASSESSMENT OF THE KNOWLEDGE AND ATTITUDE OF MOTHERS TOWARDS POSTPARTUM DEPRESSION IN SELECTED SAGAMU COMMUNITY HEALTH CENTERS, OGUN STATE. A CROSS-SECTIONAL STUDY. - Leslie, Tabitha; Adeleye, victoria; Danlami, Leslie; Okeh, Dominic (Student’s Journal of Health Research Africa, 2024)
Background Postpartum depression (PPD) is of significant public health concern due to the alarming prevalence and adverse consequences among women globally. This study assessed the knowledge and attitudes of mothers towards postpartum depression in selected health care centers in Sagamu community health centers in Ogun State. Methods The study utilized a cross-sectional quantitative design. 152 women were selected for the study, a researcher-developed questionnaires were used to collect data from respondents. SPSS version 25 was used for data analysis, and descriptive and inferential statistics were used to present the findings of the study. Results Findings from the study revealed that most of the respondents 40.8% were between the ages of 21-25 years old. The majority (66.4%) of the respondents were knowledgeable about postpartum depression and only 58.5% of the respondents indicated a positive attitude toward postpartum depression. Stressful life events during the postpartum period, financial difficulties, sleep deprivation, and traumatic birth experiences were identified as factors responsible for PPD having over 80%. Furthermore, findings also revealed that there is a relationship between the knowledge and attitude of mothers towards postpartum depression (r=0.516, p-values=0.000). Conclusion In conclusion, mothers in the two selected Sagamu community health centers had a high level of knowledge and only about half had positive attitudes towards the knowledge of PPD. Recommendation There should be an increase in awareness of postpartum depression by healthcare providers among mothers, especially during antenatal visits to reduce stigma and promote help-seeking behavior to improve maternal and child health. Moreover, partners and family members can support and encourage women dealing with postpartum depression.